ENGLISH READING MOTIVATION, STRATEGIES, ATTITUDE, AND INTEREST OF STATE JUNIOR HIGH SCHOOL STUDENTS - Machdalena Vianty; Amrullah Amrullah; Fiftinova Fiftinova (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2019)
Abstract: The objective of this study was to investigate English reading motivation, reading strategy, reading attitude and reading interest of junior high school students (Year 7, 8 and 9) in Palembang. The sample of this study was three-hundred students selected randomly from ten schools. In accordance with quantitative research design, English reading motivation, reading strategy, reading attitude and reading interest questionnaires were used as the instruments to collect the data which were statistically analyzed. The findings of this study showed that the students demonstrated a high level of English reading motivation; specifically, their instrumental motivation for reading was higher than the integrative one. Next, there was a high use of reading strategies, with Problem-Solving reading strategy as the highly used ones. The finding also revealed that the students demonstrated a positive reading attitude and their reading interest showed their reading preference was adventure stories. Keywords: English reading motivation, reading strategies, reading attitude, reading interest, self-efficacy, junior high school students